Analisis Faktor-Faktor yang Mempengaruhi Jumlah Kematian Ibu di Provinsi Maluku dengan Menggunakan Regresi Poisson - Salmon N. Aulele; Astrid G. Heumasse; Yopi Andry Lesnussa (Universitas Pendidikan Indonesia (UPI), 2021)
The statistical method used to model the relationship between the response variable (Y) and one or more independent variables (X) is regression analysis. Linear regression equations are used to analyze the response variables in the form of continuous random variables and follow a normal distribution, however, many response variables are found that are not normally distributed and are not linear in parameters becausethe mortality rate for mothers and babies always increases from year to year. The number of maternal deaths that occurred in Maluku province is an example of data count. Poisson regression is a nonlinear regression analysis of the Poisson distribution which is generally used in analyzing discrete (count) data. The purpose of this study was to determine the factors that significantly affect maternal mortality in Maluku Province using Poisson Regression, The results of this study indicate that the factors that significantly influence the number of maternal deaths in Maluku Province are the number of health centers and medical personnel in each regency / district. City (X1), the percentage of female population with education that has completed at least SD per Regency / City (X2), the frequency coverage of K4 services for pregnant women in each Regency / City (X3), and the percentage of immunization coverage for pregnant women in each Regency / City (X4).Keywords: Maternal Mortality, Poisson Regression, Regression Analysis. AbstrakMetode statistika yang digunakan untuk memodelkan hubungan antara variabel respons (Y) dengan satu atau lebih variabel bebas (X) adalah analisis regresi. Persamaan regresi linear digunakan untuk menganalisis variabel respons yang berupa peubah acak kontinu dan mengikuti distribusi normal, namun banyak ditemukan variabel respons yang tidak berdistribusi normal dan tidak linear dalam parameter. Jumlah kematian ibu yang terjadi di provinsi Maluku merupakan salah satu contoh data count. Regresi Poisson merupakan analisis regresi nonlinear dari distribusi Poisson yang umumnya digunakan dalam menganalisis data diskrit (count). Tujuan dari penilitian ini adalah untuk mengetahui faktor-faktor yang signifikan mempengaruhi jumlah kematian ibu di Provinsi Maluku dengan menggunakan Regresi Poisson. Hasil penelitian ini menunjukan bahwa Faktor-faktor yang signifikan mempengaruhi jumlah kematian ibu di Provinsi Maluku adalah jumlah puskesmas dan tenaga medis tiap Kabupaten/Kota (X1), persentase penduduk perempuan dengan pendidikan yang ditamatkan minimal SD tiap Kabupaten/Kota (X2), cakupan frekuensi pelayanan K4 bagi ibu hamil tiap Kabupaten/Kota (X3), dan persentase cakupan imunisasi bagi ibu hamil tiap Kabupaten/Kota (X4).